016 A Comparison of injuries between male and female amateur rugby union players. (3rd March 2020) - Yeomans, Caithriona; Comyns, Thomas M; Cahalan, Roisin; Warrington, Giles D; Harrison, Andrew J; Purtill, Helen; Lyons, Mark; Campbell, Mark J; Glynn, Liam G; Kenny, Ian C
Abstract : Background: Rugby participation rates are rising, particularly in the female game where a 60% increase in player numbers was observed from 2013 to 2017. Despite the recent growth, the female amateur game is lacking comprehensive long-term injury surveillance. Objective: To compare injuries in male and female amateur Rugby Union. Design: Prospective cohort study. Setting: Irish amateur clubs, during seasons 2017/18 (n=15 male clubs, 4 female) and 2018/19 (n=25 male clubs, 7 female). Participants: Male (n=958) and female (n=234) amateur players. Independent variables: Match exposure. Main outcome measurements: Match injury incidence and severity. Results: Overall incidence rates were 47.7 and 35.4/1, 000 player hours for males and females respectively. Similarities existed between males and females regarding common diagnoses and injury occurrence, with 58% of injuries occurring during the tackle. Concussion and ankle lateral ligament injuries were the most common diagnoses for both males (5.5 and 4.1/1, 000 player hours) and females (5.5 and 3.9/1, 000 player hours). However differences showed females suffering more injuries in the ruck compared to males (6.1 vs 3.8/1, 000 player hours) while males sustained more non-contact injuries compared to females (4.7 vs 1.4/1, 000 player hours). Females showed an earlier injury occurrence in the 2nd quarter (9.4/1, 000 player hours) plateauing into the 3rd and 4th quarters, whereas males had a 3rd quarter injury peak (15.2/1, 000 player hours). Concussion had the highest injury burden in males (190 days/1, 000 player hours), while anterior cruciate ligament injuries had the highest burden (307 days/1, 000 player hours) in females. Conclusions: Long-term prospective injury surveillance is vital to inform targeted prevention strategies. The earlier occurrence of injury in females should be investigated further to determine whether player substitution strategies may decrease injuries. Prevention strategies incorporating neuromuscular training should be considered, given the high rate of ankle ligament injuries in both males and females, and the burden of knee ligament injuries in females.